Community resilience – Systems and approaches in remote settlements. (December 2022) - Taarup-Esbensen, Jacob
Abstract: This paper explores community resilience to climate-related disasters in the Arctic using the example of a tsunami event in the Uummannaq fjord systems. In 2017 the fjord experienced an avalanche-induced tsunami that devastated one settlement while another was abandoned. Investigations revealed unstable cliff sides at two nearby sites that could trigger large avalanches. The result of another event could be waves of up to 23 m. A model for community resilience is presented and explored through onsite observations, maps, archival material and interviews. The analyses show what impact such events can have on the communities in the fjord system and the current level of community resilience. Such an event will also affect long-term liveability, leading to the potential abandonment of settlements. Especially the effect on critical infrastructures like access to energy, telecommunication, fuel, freshwater, food and healthcare will significantly reduce liveability. A collectivistic culture, local knowledge and the level of trust among community members somewhat mitigate these effects but will not offset the general lack of preparedness. In order to ensure sustained liveability in the six remaining communities, there is a need for investments in the relocation of critical infrastructure, emergency preparedness planning and the recovery of critical activities.